Nano-ballistic saturation Velocity modelling to enhance circuit performances of Nano-Mosfet - Ismail Saad (Universiti Malaysia Sabah, 2010)
The modeling of nano-ballistic carrier transport nature across the nanoscale channel of a MOSFET based on streamlining of the randomly oriented velocity vectors in the presence of high electric field has been successfully done in this project. Detailed explanation of low-dimensional energy spectrums and carrier statistics for quasi 3D, 20 and 10 that invoked the quantum effects and the Fermi energy distributions in non-degenerate and degenerate region essential for nanoscale transistor was found respectively. The ballistic intrinsic velocity for Q3D, Q20 and QID system has been derived for non-degenerate and degenerate regime and analyzed its dependence towards temperature and carrier concentrations. Based on ballistic velocity field characteristics, the current-voltage (I-V) characteristics of a 20 nanoscale MOSFET has been derived successfully. The gate quantum confinement (QC) effects is analyzed and applied to the modeling of nano-MOSFET. The innovative linear and saturation region of drain current expresSions of a nanoscale MOSFET is explained based on electric-field profiles at the source and drain end. A very well agreement of the theory applied and models developed with 80nm channel length fabricated MOSFET validates the explained physics based theory of a nano-ballistic carrier transport.